PENGARUH PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN ANGGOTA KSPPS BMT DRI MUAMALAT JAWA TENGAH DI KABUPATEN TEGAL - Rizqoh, Itsna Tifani Barokatur (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Basically customer satisfaction includes service levels and perceived performance. Starting from the complaints felt by BMT DRI Muamalat members regarding the service and performance of KSPPS DRI Muamalat Central Java employees in Tegal Regency, this research was conducted to determine the extent of the influence of service and employee performance carried out by BMT DRI Muamalat employees on member satisfaction. This study is aims to determine the influence of employee’s service and performance to member’s satisfaction of KSPPS BMT DRI Muamalat Jawa Tengah di Kabupaten Tegal. Employee’s service and performance are the the independent variable. Whereas member’s satisfaction is the dependent satisfaction. This type of research uses a quantitative approach to test the theory about satisfaction.  The population in this study was all the member of KSPPS BMT DRI Muamalat in the year 2021. Sampling design that used was probability sampling by incidental technique which produce 92 respondents. So, every member of KSPPS BMT DRI Muamalat in the year 2021 that met randomly can be respondent. A quistionnare is used for colleting the data that needed that had been tested for the validity and reliability. Data analysis used multiple linear regression, coefficient of determination, simultaneous F test, partial t test) and estimation of coefficient parameter values. The result of this research indicate that, employee’s service has a positive and significant effect on member’s satisfaction of KSPPS BMT DRI Muamalat by the t-test 3,628>1,987 and a significance of 0,000<0,05. Whereas employee’s performance has a positive and significant effect too on member’s satisfaction of KSPPS BMT DRI Muamalat by the t-test 7,684>1,987 and a significance of 0,000<0,05.